Automated Health Services Reprogramming the Doctor - Day, E. (Methods of Information in Medicine, 1970)
The autor surveys the potential impact of modern technology on the practice of preventive and diagnostic medicine. The experience of Strang Clinic in cancer detection during the past three decades is briefly reviewed as a base for the »new look« in clinical services. With the broadening of scope to include all major diseases, and the demand to serve more of the population, new methods of data acquisition and processing are now essential. The paper reviews future goals and the available methods of attaining them.